ETHICAL LEADERSHIP AND RESPONSIBLE MANAGEMENT AS LEVERS FOR IMPROVEMENT IN SECURITY, EMERGENCY AND DEFENCE ORGANISATIONS - García-Guiu, Carlos (Journal of the Spanish Institute for Strategic Studies, 2018)
Society expects the heads of institutions to uphold an ongoing ethicalcommitment and to manage public and private organisations with thegreatest level of responsibility possible. This expectation is reflected inlegislative reforms in Spain and in the growing implementation of thecurrent Spanish strategy for social responsibility by the Public Administration.This paper sets out the proactive role that ethical leadership and socialresponsibility should play as two levers for improvement in the runningand management of security and defence institutions in Spain, as wellas for helping to promote the commitment, innovation and quality ofpublic services.The exercise of ethical leadership is based on justice, respect for people,transparency, participation and sustainability. A culture of responsibilityshould be developed in line with the current Spanish strategy forsocial responsibility in order to foster the improvement of institutionsat all levels, an increase in efficiency, and the provision of a better serviceto society